Influence of the Coronavirus Disease 2019 Pandemic on Patients with ST-Segment Elevation Myocardial Infarction in Taiwan. (16th April 2021) - Su, Yuan-Heng; Wu, Kuan-Han; Su, Chih-Min; Cheng, Chi-Yung; Cheng, Cheng-I; Kung, Chia-Te; Chen, Fu-Cheng
Abstract : The outbreak of the new coronavirus disease 2019 (COVID-19) has notably affected the medical system worldwide and influenced the health-seeking behavior of people while depleting medical resources, causing a delay in ST-elevation myocardial infarction (STEMI) management. In this single-center, retrospective cohort study, we compared the clinical pictures of nontransfer patients who presented to the emergency department directly and received primary percutaneous cardiovascular intervention (PPCI) from February 1 to April 30, 2020 (group 2, N  = 28), with patients who received PPCI from February 1 to April 30, 2016–2019 (group 1, N  = 130). A total of 158 patients with STEMI who received PPCI were included in the study. A decrease in the percentage of patients with door-to-balloon time <90 minutes was found in group 2 (64.3% vs. 81.5%, p  = 0.044). The adjusted odds ratio was calculated using logistic regression, according to potential confounding factors such as age, sex, off-hours, and Killip class. An adjusted odds ratio of 2.45 (95% confidence interval, 1.1–6.0, p  = 0.048) was reported for group 2. A decrease in the percentage of patients meeting the criteria of door-to-balloon time <90 minutes was demonstrated, and differences were revealed in the clinical pictures of patients with STEMI after the pandemic. While systemic factors contributed the most, improvements and adjustments in the protocols for managing patients with STEMI for better outcomes in the COVID-19 era have yet to be studied.